Acceleration of the parameters identification for dynamic models construction using parallelization - Byczkowska-Lipińska, Liliana; Stakhiv, Petro; Kozak, Yuriy (Publishing House of Lviv Polytechnic National University, 2012)
Construction of mathematical models for nonlinear dynamical systems using оptimization requires significant computation efforts to solve the optimization task. This makes it reasonable to use parallelization of calculations for optimization task solving, especially taking into account current tendency for increasing the number of CPU cores in a single chip. The effectiveness of particular parallel implementation of optimization process is the subject of investigation in this paper. Побудова математичної моделі нелінійних динамічних систем з використанням оптимізації вимагає значних обчислювальних затрат для вирішення задачі оптимізації. Це робить доцільним використовувати розпаралелення обчислень для вирішення завдань оптимізації, особливо з урахуванням поточної тенденції збільшення числа процесорних ядер в одному чіпі. Ефективність зокрема паралельної реалізації процесу оптимізації є предметом дослідження в даній роботі.
Пришвидшення параметричної ідентифікації для побудови динамічних моделей з використанням розпаралелення
Keywords: macromodels; optimization; parallelization